Special Education at the Crossroad: An Identity Crisis and the Need for a Scientific Reconstruction. Issue 2 (3rd April 2017) - Kauffman, James M.; Anastasiou, Dimitris; Maag, John W.
ABSTRACT: Special education is losing its identity—its visibility, distinctiveness, budget, and basic functions are all at risk. Special education functions include (a) sorting, categorizing, and labeling students who need it; (b) making the right comparisons; (c) honoring diversity but changing particular differences; (d) managing stigma; (e) making subjective judgments and risking errors; (f) dealing with students' failures; and (g) adequate financing in addition to maintaining visibility and status and having its own budget and personnel. It cannot exist without these functions, all of which are criticized or on the decline. Special education must also be reconstructed on the basis of sound science, not alternative narratives or nonscientific ways of knowing that do not help students with disabilities learn all they can. The need for a scientific reconstruction and implications for special education's future are discussed.